Abuse of right - Svetlana Shevchuk (Laplage em Revista, 2021)
Based on studying and analyzing the norms inherent in the institution of the abuse of right and legal opinions by scholars of civil jurisprudence and legal precedents, the authors explore the essence of the legal category "the abuse of right". The authors define the meaning of the novels in Article 10 of the Civil Code of the Russian Federation and identify the drawbacks, gaps, and contradictions in the institution of the abuse of right. The authors analyze the theoretical, practical, and social issues affecting the rights and interests of participants in social relations when the right is abused. The relevance and the need for further development and improvement of the institution of the abuse of rights are justified.